1994
DOI: 10.1083/jcb.126.3.713
|View full text |Cite
|
Sign up to set email alerts
|

Lipids trigger changes in the elasticity of the cytoskeleton in plant cells: a cell optical displacement assay for live cell measurements.

Abstract: Abstract. An assay has been developed to quantitatively measure the tension and elasticity of the cytoskeleton in living plant cells. The cell optical displacement assay (CODA) uses a focused laser beam to optically trap and displace transvacuolar and cortical strands through a defined distance within the cell. Results from these experiments provide evidence for the classification of at least two rheologically distinct cytoskeletal assemblies, cortical and transvacuolar, that differ in their tension and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 73 publications
3
46
0
Order By: Relevance
“…Cells were permeabilized and stained with Bodipy-phallacidin (F-actin-specific fluorescent probe) (Molecular Probes, Eugene, OR) as described (Grabski et al, 1994). A total of 25 sections (at 0.5-pm intervals) were accumulated and examined.…”
Section: Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were permeabilized and stained with Bodipy-phallacidin (F-actin-specific fluorescent probe) (Molecular Probes, Eugene, OR) as described (Grabski et al, 1994). A total of 25 sections (at 0.5-pm intervals) were accumulated and examined.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…CODA was performed as described by Grabski et al (1994) and Schindler (1995). Briefly, a soybean (Glycine max [L.] Merr.…”
Section: O D Amentioning
confidence: 99%
See 1 more Smart Citation
“…Both linoleic and linolenic acids stimulate the abscission of bean petiole explants (Ueda et al, 1991). Recently, it has been shown that treatments of soybean cells with linoleic acid results in pronounced changes in cytoskeletal organization (Grabski et al, 1994). In vitro, free fatty acids elicit a number of effects.…”
Section: Suttlementioning
confidence: 99%
“…Optical tweezers use laser light to produce non-contact forces in the piconewton range, and are capable of positioning small particles with submicrometer accuracy (for reviews, see Svoboda and Block, 1994;Hoffmann, 1996;Sheetz, 1998). Intracellular forces have previously been indirectly measured using organelles trapped in a focused laser beam (Ashkin and Dziedzic, 1989;Grabski et al, 1994;Schindler, 1995;Felgner et al, 1996), but the force was not calibrated.…”
mentioning
confidence: 99%